Home Care for the Elderly: An Integrated Approach to Perception, Quality of Life, and Cognition - Genaro, Luis Eduardo [UNESP]; Marconato, José Victor; Tagliaferro, Elaine Pereira da Silva [UNESP]; Pinotti, Felipe Eduardo [UNESP]; Valsecki Júnior, Aylton [UNESP]; Adas Saliba, Tânia [UNESP]; Rosell, Fernanda Lopez [UNESP] (MDPI, 2024)
This study investigated the impact of home care, health status, and cognition. A qualitative and quantitative approach was employed through a cross-sectional study with a sample of 60 elderly individuals in need of home care in the municipality of Itatiba, São Paulo, Brazil. The analysis utilized the Discourse of the Collective Subject (DCS), EQ-5D, EQ VAS, and Mini-Mental State Examination (MMSE). The sample consisted of 40.0% male and 60.0% female individuals. The majority (61.6%) received weekly visits, mainly from community health agents, who were responsible for the majority of the care (45%). Positive considerations were highlighted, with 36.6% emphasizing the contribution to treatment continuity. The EQ VAS assessment indicated a moderately good perception of health. The EQ-5D analysis revealed significant differences between genders in personal care (p = 0.04). There were significant differences between clinical characteristics and EQ-5D dimensions, such as neoplasia and reduced mobility (p = 0.04), and arthritis/osteoarthritis/rheumatism and a limitation in common activities (p = 0.01). The presence of anxiety/depression was significant in cases of neoplasia (p = 0.006), arthritis/osteoarthritis/rheumatism (p = 0.01), and stroke (p = 0.04). The logistic regression analysis showed associations between usual activities and arthritis, osteoarthritis, rheumatism (p = 0.034), pain/malaise and arthritis, osteoarthritis, rheumatism (p = 0.038), and anxiety/depression and stroke (p= 0.028). The average MMSE scores (17.52) suggested a mild cognitive impairment, with no statistical differences between genders. Based on these results, it can be concluded that home care can provide a comprehensive approach and continuous assistance, emphasizing the importance of personalized care based on perceived and clinical differences.
Keywords: home care services; home nursing; mini-mental state examination